Free science under threat: The current revival of Bernalism and the use of market‐based scientific practices are undermining science as we know it. (21st December 2015) - Rull, Valentí
Abstract : In the 1930s, under the influence of Marxism, John Bernal and others proposed that the state should wholly control the goals of science. Such control never came to pass in the West, but a modern version of Bernalism is again threatening the freedom of research, hiding under the guise of requiring scientists to address societal problems.